Organic vapor sensing properties of copolymer Langmuir-Blodgett thin film sensors. Issue 8 (2nd August 2016) - Acikbas, Y.; Dogan, G.; Erdoğan, M.; Çapan, R.; Soykan, C.
ABSTRACT: In this study, a novel poly[Styrene (ST)-co-Glycidyl Methacrylate (GMA)] copolymer material is used to fabricate Langmuir-Blodgett (LB) thin films and investigate organic vapor sensing properties. Quartz Crystal Microbalance (QCM) system is used to investigate gas sensing performance of copolymer LB films during exposure to Volatile Organic Compounds (VOCs). The poly[Styrene (ST)-co-Glycidyl Methacrylate (GMA)] LB thin film sensor sensitivities are determined to be between 0.12 and 0.25 Hz ppm −1 . Detection limits of the copolymer LB thin film are found to be between 23 and 49 ppm against organic vapors. The copolymer LB thin films are more sensitive to chloroform than other vapors used in this study. The results demonstrated that the poly[Styrene (ST)-co-Glycidyl Methacrylate (GMA)] copolymer material is promising as a organic vapor sensing device at room temperature.